Time-Varying and Constant Switching Frequency-Based Sliding-Mode Control Methods for Transformerless DVR Employing Half-Bridge VSI - Komurcugil, Hasan; Biricik, Samet (IEEE-Inst Electrical Electronics Engineers Inc, 2017)
This paper presents time-varying and constant switching frequency based sliding-mode control (SMC) methods for three-phase transformerless dynamic voltage restorers (TDVRs) which employ half-bridge voltage source inverter. An equation is derived for the time-varying switching frequency. However, since the time-varying switching frequency is not desired in practice, a smoothing operation is applied to the sliding surface function within a narrow boundary layer with the aim of eliminating the chattering effect and achieving a constant switching frequency operation. The control signal obtained from the smoothing operation is compared with a triangular carrier signal to produce the pulse width modulation signals. The feasibility of both SMC methods has been validated by experimental results obtained from a TDVR operating under highly distorted grid voltages and voltage sags. The results obtained from both methods show excellent performance in terms of dynamic response and low total harmonic distortion (THD)in the load voltage. However, the constant switching frequency-based SMC method not only offers a constant switching frequency at all times and preserves the inherent advantages of the SMC, but also leads to smaller THD in the load voltage than that of time-varying switching frequency-based SMC method.
Keywords: Constant switching frequency; dynamic voltage restorer (DVR); sliding-mode control (SMC); time-varying switching frequency